The Teachers' Pedagogic Competence in Teaching English through Online and Offline Setting - Nur Fadila Faidal; Rafi'ah - Nur; Suriani Suriani (Universitas Negeri Makassar, 2020)
Nowadays, a new trend in the teaching and learning process emerges along with the development of technology. This study aims at exploring the pedagogical competence of English teachers at SMPN 8 Satap Maiwa. It also aims at finding out the students' perceptions of their teachers' pedagogical competence. There were three kinds of instruments in this study. They were observation, interview, and a questionnaire. Based on the interviews, the results showed that the teachers enjoyed teaching in the classroom, and they were interested in conducting online instruction even sometimes found problems in doing the process. Based on the questionnaire, the researcher found students perceived their teachers as quite good instructors in the classroom. Finally, the researchers suggested to the teachers that they should always intend to improve their competence by applying some new methods to make students better understand the materials.